GlyT2-Dependent Preservation of MECP2-Expression in Inhibitory Neurons Improves Early Respiratory Symptoms but Does Not Rescue Survival in a Mouse Model of Rett Syndrome - Hülsmann, Swen; Mesuret, Guillaume; Dannenberg, Julia; Arnoldt, Mauricio; Niebert, Marcus (Frontiers in Physiology, 2016)
Mutations in methyl-CpG-binding protein 2 (MECP2) gene have been shown to manifest in a neurodevelopmental disorder that is called Rett syndrome. A typical problem that occurs during development is a disturbance of breathing. To address the role of inhibitory neurons, we generated a mouse line that restores MECP2 in inhibitory neurons in the brainstem by crossbreeding a mouse line that expresses the Cre-recombinase (Cre) in inhibitory neurons under the control of the glycine transporter 2 (GlyT2, slc6a5) promotor (GlyT2-Cre) with a mouse line that has a floxed-stop mutation of the Mecp2 gene (Mecp2stop/y). Unrestrained whole-body-plethysmography at postnatal day P60 revealed a low respiratory rate and prolonged respiratory pauses in Mecp2stop/y mice. In contrast, both frequency and ventilatory pauses in GlyT2-Cre positive Mecp2stop/y mice (Cre+; Mecp2stop/y) showed greatly improved respiration and were indistinguishable from wild type littermates. This data supports the concept that alterations in inhibitory neurons are important for the development of the respiratory phenotype in Rett syndrome.